Reductive hydrogenation under single-site control: generation and reactivity of a transient NHC-stabilized tantalum(III) alkoxide - Mörsdorf, Jean-Marc; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2021)
One of the most attractive routes for the preparation of reactive tantalum(III) species relies on the efficient salt-free hydrogenolysis of tantalum(V) alkyls or tantalum(V) alkylidenes, a process known as reductive hydrogenation. For silica-crafted tantalum alkyls and alkylidenes, this process necessarily proceeds at well-separated tantalum centers, while related reductive hydrogenations in homogeneous solution commonly involve dimeric complexes. Herein, an NHC scaffold was coordinated to a novel tri(alkoxido)tantalum(V) alkylidene to circumvent the formation of dimers during reductive hydrogenation. Employing this new model system, a key intermediate of the process, namely a hydrido-tantalum alkyl, was isolated for the first time and shown to exhibit a bidirectional reactivity. Upon being heated, the latter complex was found to undergo either an alpha-elimination or a reductive alkane elimination. In the (overall unproductive) alpha-elimination step, H-2 and the parent alkylidene were regenerated, while the sought-after transient d(2)-configured tantalum(III) derivative was produced along the reaction coordinate of the reductive alkane elimination. The reactive low-valence metal center was found to rapidly attack one of the NHC substituents via an oxidative C-H activation, which led to the formation of a cyclometalated tantalum(V) hydride. The proposed elemental steps are in line with kinetic data, deuterium labeling experiments, and density functional theory (DFT) modeling studies. DFT calculations also indicated that the S = 0 spin ground state of the Ta(III) center plays a crucial role in the cyclometalation reaction. The cyclometalated Ta(V) hydride was further investigated and reacted with several alkenes and alkynes. In addition to a rich insertion and isomerization chemistry, these studies also revealed that the former hydride may undergo a formal cycloreversion and thus serve as a tantalum(III) synthon, although the original tantalum(III) intermediate is not involved in this process. The latter reactivity was observed upon reaction with internal alkynes and led to the corresponding eta(2)-alkyne derivatives via vinyl intermediates, which rearrange via a remarkable, hitherto unprecedented, hydrogen shift reaction.
Gesehen am 04.08.2021